Cost and Schedule Overruns in Construction Projects An internal study on how to manage the key factors causing project overruns - DAOUD RAJHA, MARIA; HAMA, HONNIA (My University, 2020)
For several years, proper cost and time estimations of construction projects have been a prevailing issue in construction industry. Despite the efforts made to prevent overruns within construction projects through the proposition of new estimating models and methods, project cost overruns and delays continue to occur with the same frequency. To manage project overruns, coupled with the fact that having the right cost and time estimation is crucial in order to achieve success in different kind of construction projects. This report aims to identify the internal key factors causing cost and schedule overruns and to investigate how these internal key factors affect and lead to overruns in a Swedish construction company. By addressing these factors, the study aims to find practical controlling mechanisms for managing and preventing project overruns from occurring. A review of literature including eleven internal key factors considered to be the most common internal contributing factors have been identified. A qualitative research based on interviews with different managers at the company has been conducted. Besides, A quantitative research based on survey has also been adopted in order to collect more relevant data for obtaining a more realistic result. The empirical findings indicated that the most influential key factors was poor planning, lack of experience and ineffective communication. Therefore, in order to avoid the identified internal key factors causing project overruns, using the RCF method, having experience feedback sessions, bridging production with tender and improvements of site management should be embraced.
Keywords: construction industry; construction projects; cost overruns; time delays; Reference Class Forecasting